Making vision into power : Britain's acquisition of the world's first radar-based integrated air defence system 1935 - 1941 - Judkins, Phillip Edward (Cranfield University, 2008)
This thesis represents the first application of a current conceptual model of defence acquisition to analyse the historical process, the 1935 - 1941 British acquisition of an integrated air defence system pivoted upon the innovative technology of radar. For successful acquisition of a military capability, the model posits that balanced attention must be focused acoss eight 'lines of developmen' - not only equipment, but also doctrine and concepts, logistics, structures, personnel, organisation, training and information with an overarching requirement for interoperability. This thesis contrasts what turned out to be a successful acquisition, of radar to achive air interception capability by day in the Battle of Britain, with less successful acquisition, or radar to achieve the same capability at night, where an effective system arrived too late to ward off the Blitz. The results establish the validity of the model and its attendant lines of development concepts, and furnish new insights into acquisition processes and military history. Acquisition lessons are derived for the capability-based involvement of industry, for the experience and personality necessary for key managers at different 'life stages' of an acquisition and for the avoidance of over-rapid 'dysfunctional diffusion' of innovative technologies. Historical insights for the Battle of Britain include the sub-optimal performance, for trivial reasons, of key South Coast radars, and the critical importance of the human elements of the radar-based air defence system. For the Blitz, airborne radar hardware has previously been identified as a key problem, whereas research here exposes the greater need for accurate ground control radar, the sound selection and training of pilots and operators in new tactics, and provision of equipment maintainers and test gear. New evidence illustrates that pursuit of an alternative to radar significantly delayed the optimal solution, and throws fresh light both on personalities and on development process management.